Glycosylation changes during differentiation of the murine uterine epithelium. (May 2001) - Kimber, S. J.; Stones, R. E.; Sidhu, S. S.
Abstract : In mouse uterine luminal epithelium (LE) several terminal carbohydrate structures are regulated by ovarian steroids and show stage-specific expression during early pregnancy. We have demonstrated that expression of H-type-1 antigen (Fucα1-2Galβ1-3GlcNAcβ1-) is regulated by oestrogenic stimulation of α-2fucosyltransferase ( fut 1) mRNA levels in LE. H-type-1 expression is high after ovulation but becomes negligible after implantation. In contrast, NeuNAcα2-3Galβ1-, and specifically sialyl Le-x (NeuAcα2, 3Galβ1, 4-[Fucα1-3]GlcNAcβ1-), is stimulated by progesterone. It is not expressed on LE after ovulation but is expressed maximally on apical LE at the time of and after implantation. However, mRNA levels for 4 out of 5 known Gal/GalNAc α2-3sialyltransferases appear not to change in LE during early pregnancy, suggesting an alternative level of control.